Plasticity-induced damage and material loss in oscillatory contacts. (1st November 2022) - Cen, Jialiang; Komvopoulos, Kyriakos
Highlights: An FEM analysis of a rigid cylinder in oscillatory contact with a strain hardening half-space. Load and friction effects on plasticity-induced cumulative damage and loss of material. Results in dimensionless form showing the evolution of plasticity, damage, and material loss. A computational methodology for studying the mechanical performance of oscillatory contact devices. Abstract: Knowledge of plasticity-induced damage leading to the loss of material in oscillatory contacts is of paramount importance to various electromechanical systems comprising contact-mode elements exposed to high-frequency vibrations. However, experimental investigation of the wear behavior of devices experiencing microscopic oscillatory contact (fretting) is complex, time consuming, and expensive. More importantly, the progression of critical damage processes, such as the decrease of the material's strength with the accumulation of plastic deformation in the vicinity of the contact interface and the removal of material in the form of microscopic wear debris, cannot be tracked in real time, necessitating cumbersome and costly post-testing microanalysis. Alternatively, computational wear modeling is more effective than experiments and can provide valuable insight into the effect of important parameters, such as load, coefficient of friction, oscillation amplitude, and material behavior, on the loss of material during oscillatory sliding contact. Accordingly, the principal objective of this study was to introduce a computational approach, which can be used to analyze the loss of material due to plasticity-induced damage in oscillatory mechanical components. To achieve this aim, a plane-strain finite element model of a rigid cylinder in reciprocating sliding contact with an elastic-plastic half-space exhibiting isotropic strain hardening was used to study how the evolution of damage due to the progression of plasticity leads to the loss of material. A quasi-static, isothermal damage model based on a ductile failure criterion was implemented in the finite element analysis to simulate the removal of the fully damaged elements. Numerical results illuminate the effects of the load and coefficient of friction on the development of plasticity, cumulative damage, and loss of material with accruing oscillation cycles. The deviation of the wear behavior from classical wear theory in the high-load simulations is explained by the plastic shear strain distribution and less slip at the contact interface encountered at high loads. The novelty of this study is the development of a computational methodology, which sheds light into the evolution of plasticity, damage, and loss of material in reciprocating sliding contacts and provides an effective computational capability for assessing the effects of load, friction, and material behavior on the mechanical performance of components operating in oscillatory contact mode.